25. The effect of Fingerroot Rhizome (Boesenbergia pandurata) Extract on the Growth of Staphylococcus aureus in Vitro - Silvia P.N Keliat; Darniati Darniati; Abdul Harris; Erina Erina; Rinidar Rinidar; Fahkrurrazi Fahkrurrazi (Universitas Syiah Kuala, 2019)
This study aimed to determine the inhibitory effect and the concentration of fingerroot extract to inhibit Staphylococcus aureus growth. The data was analyzed descriptively. Ampicillin was used as positive control, distilled water was used as negative control, and the treatments were given fingerroot extract with a concentration of 5%, 15%, 25%, 35% and 45%. This study was conducted with three replications. The parameter measured was the diameter of inhibition zone formed by diffusion method. The average diameter of inhibition zone of the fingerroot extract were 15% : 10.3 mm; 25% : 13,6mm; 35% : 18,7mm; 45% ± 21,1mm, and at a concentration of 5% the inhibition zone is not formed. The final conclusion is that the fingerroot extract can inhibit the growth of Staphylococcus aureus. The higher concentration of fingerroot extract, the more extensive inhibition zone formed.